1984
DOI: 10.1111/j.1748-1716.1984.tb07483.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of centrally administered neuropeptide Y on EEG activity in different rat strains and in different phases of their circadian cycle

Abstract: The effects of centrally administered neuropeptide Y (NPY) on the sleep-wakefulness cycle have been studied by analyzing its action in different strains of rats with or without spontaneous hypertension and during two different phases of the circadian cycle. Normal adult Sprague-Dawley (SD), Wistar-Kyoto (WKy) and spontaneous hypertensive (SH) rats were used. By means of EEG electrodes the recording of the fronto-parietal electrocorticogram and the electromyogram could be made. Stainless steel cannula were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
3

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 7 publications
4
21
3
Order By: Relevance
“…In contrast, previous studies found that intracerebroventricular injection of NPY induced the slowing of highfrequency theta activity simultaneously with the speeding up of low-frequency theta waves in cortex, hippocampus, and amygdala in rats (11). Two studies from the same research group found increased synchronized and mixed EEG activity after central administration of NPY in rats (12,49). The differences between the results of the studies above and ours may be because of the different experimental conditions.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In contrast, previous studies found that intracerebroventricular injection of NPY induced the slowing of highfrequency theta activity simultaneously with the speeding up of low-frequency theta waves in cortex, hippocampus, and amygdala in rats (11). Two studies from the same research group found increased synchronized and mixed EEG activity after central administration of NPY in rats (12,49). The differences between the results of the studies above and ours may be because of the different experimental conditions.…”
Section: Discussioncontrasting
confidence: 42%
“…In one study, visual inspection of the electroencephalograms (EEG) suggested that NPY induces a reduction in desynchronized EEG activity and an increase in synchronized and mixed activity in rats (49). Ehlers at al.…”
mentioning
confidence: 99%
“…Central NPY in rodents results in enhanced sleep continuity and electroencephalographic synchronization, 109,110 probably linked with reduced NE and 5-HT (5-hydroxytryptamine) release in the locus coeruleus and dorsal raphe, respectively. NPY-containing neurons in the basal forebrain (BF) are slow-wave sleep-active cells.…”
Section: Hyperarousalmentioning
confidence: 99%
“…In mammals, a variety of central functions have been proposed for NPY (Albers and Ferris, 1984;Zini et al, 1984). Biological effects include stimulation of food intake (Clark et al, 1984;Leibowitz, 1984, 1985;, modulation of various cardiovascular and respiratory parameters (Fuxe et al, 1983;Hä rfstrand et al, 1984;Hä rfstrand, 1986), and stimulation of insulin secretion (Moltz and McDonald, 1985;Kuenzel, 1988).…”
mentioning
confidence: 98%